The Influence of the International Press and Foreign Correspondents in Transitional Democracies: The role of the Anglo-American journalists during post-Francoist Spain (1975–1978). (4th March 2017) - Tulloch, Christopher; Mauri, Marcel; Guillamet, Jaume
Abstract : The intersection between journalism and political transitions in contemporary history is a research field which has begun to flourish in recent years. From the "Carnation Revolution" in Portugal in 1974 through to post-apartheid South Africa in the early 1990s and up to the so-called "social media revolutions" of the Arab Spring of 2011, both historical and comparative political studies have considered the international press to play an integral role in these processes of democratic change. In this context of regime change, the Spanish transition to democracy (1975–1978) is often portrayed as the most exemplary case study. This article analyses the role played by the foreign correspondents of the British and American broadsheets and wire services sent to cover events in Spain as well as the contribution made by the Anglo-American press through its editorial stance on key issues and its commitment to the story both in terms of journalistic output and human resources. The article suggests that the role of the international press not only offers a useful connecting route to those charged with making foreign policy decisions and monitoring the state of public opinion in their respective capitals—in this case London and Washington—but can also make an indirect contribution to the sway of political events at a domestic level.